THE INFLUENCE OF MIND MAPPING METHOD AND LEARNING MOTIVATION TOWARDS THE EIGHT GRADE STUDENTS` WRITING ABILITY ON DESCRIPTIVE TEXTS AT ISLAMIC JUNIOR HIGH SCHOOL TWO OF PALEMBANG - Hendra Gunawan; Tahrun Tahrun; Magdad Hatim (ELTE Journal (English Languange Teaching and Education), 2020)
This research was concerned with the influence of the mind mapping method and learning motivation towards students` writing ability on descriptive texts at Islamic Junior High School Two of Palembang in the academic year 2019/2020. Sixty students of the eighth grade were chosen as samples utilizing two stages of random sampling. This study applied the factorial research design. The data were collected by using questionnaires and tests. The data were analyzed by using Normality, Homogeneity, Independent Sample t-test, and Two-Way ANOVA. The results showed that, first, there was a significant difference in students’ writing ability on descriptive texts for the students who have high learning motivation with the students who have low learning motivation taught by using the mind mapping method, Second, there was a significant difference on students’ writing ability on descriptive texts for the students who have high learning motivation taught by using mind mapping and conventional method. Third, there was a significant difference in students’ writing ability for the students who had low learning motivation taught by using the mind mapping method and the conventional method. Fourth, there was a significant difference in students’ writing ability on descriptive texts for the students who have high learning motivation with the students who have low learning motivation taught by using the conventional method, finally, there were significant interaction effects of learning motivation on students’ writing ability on descriptive text taught by using mind mapping method and learning motivation at Islamic Junior High School Two of Palembang. So, the mind mapping method could be better used for teaching descriptive texts at Islamic. Junior High School Two of Palembang